2021
DOI: 10.1186/s12957-021-02406-z
|View full text |Cite
|
Sign up to set email alerts
|

The decreased platelet-to-lymphocyte ratio could predict a good prognosis in patients with oligometastatic colorectal cancer: a single-center cohort retrospective study

Abstract: Background Inflammation markers have an important effect on tumor proliferation, invasion, and metastasis. Oligometastatic disease (OMD) is an intermediate state between widespread metastases and locally confined disease, where curative strategies may be effective for some patients. We aimed to explore the predictive value of inflammatory markers in patients with oligometastatic colorectal cancer (OMCC) and build a nomogram to predict the prognosis of these patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Studies have shown that preoperative MPV/TPC in the peripheral blood of CRC cases is low, 53 , 57 High levels of pretreatment TPC to lymphocyte count ratio (PLR) is associated with poor overall survival in CRC patients, 58 and decreased TPC/PLR shows good prognosis in patients with oligometastatic colorectal cancer. 59 MPV/TPC was associated with tumor infiltration and regional lymph node metastasis in CRC. 53 TPC/PLR was associated with depth of infiltration, 60 and this infiltration was associated with poor prognosis in postsurgical CRC patients.…”
Section: Cancer and Plateletsmentioning
confidence: 92%
“…Studies have shown that preoperative MPV/TPC in the peripheral blood of CRC cases is low, 53 , 57 High levels of pretreatment TPC to lymphocyte count ratio (PLR) is associated with poor overall survival in CRC patients, 58 and decreased TPC/PLR shows good prognosis in patients with oligometastatic colorectal cancer. 59 MPV/TPC was associated with tumor infiltration and regional lymph node metastasis in CRC. 53 TPC/PLR was associated with depth of infiltration, 60 and this infiltration was associated with poor prognosis in postsurgical CRC patients.…”
Section: Cancer and Plateletsmentioning
confidence: 92%
“…Multiple factors have been reported to be associated with survival outcomes, with tumor number being one of these [20,[27][28][29][30][31][32]. Large tumor numbers indicated poor tumor behavior.…”
Section: Comparison Of Scoring Systems Built After Stratification And...mentioning
confidence: 99%
“…In addition, the systemic inflammatory response also plays a vital role in cancer occurrence and progression, since cancer-associated inflammatory mediators aid in lymphovascular invasion, suppression for immune effector cells, and immune escape [ 17 19 ]. Several immune and systemic inflammation-associated biomarkers have been reported to be associated with long-term prognosis and postoperative complications such as anastomotic leakage in CRC [ 20 24 ]. Among these biomarkers, the lymphocyte counts, Glasgow prognostic score (GPS), modified GPS (mGPS), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte-ratio (LMR), platelet-to-lymphocyte ratio (PLR), and C-reactive protein to albumin ratio were commonly used to predict CRC outcomes or therapeutic response [ 19 , 25 32 ].…”
Section: Introductionmentioning
confidence: 99%